Analysis of Islamic Business Ethics in Buying and Selling Transactions of Agricultural Products Using a Wholesale System and Its Impact on Farmers’ Income in Tanjung Kenongo Village, Pacet District, Mojokerto Regency - Prasetyo, Dzulfikar Wahyu; Toha, Mohamad (Danadyaksa: Post Modern Economy Journal, 2023)
When carrying out good buying and selling, it should be based on likes and mutual approval in order to receive blessings from Islamic teachings. Farmers’ income is generally uncertain, it can be once a month or even months and there is still uncertainty about the potential for losses and there are still times when they have to wait for a long time until the harvest season arrives. The impact of buying and selling agricultural produce transactions using a contract system on farmers’ income. Islamic Business Ethics in Sales and Purchase Transactions of Agricultural Produce using a Wholesale System in Tanjung Kenongo Village. In this research, the researcher used a descriptive qualitative approach using a type of field research, namely research in the field or field research. In collecting data in this research, the data used came from direct interviews with related sources. In this contract system, of course, farmers feel a little disadvantaged because they cannot make large profits considering that fertilizer prices are expensive, accommodation costs such as expensive farm laborers, and the price of basic necessities increase so that farmers cannot make a lot of profit, their income decreases a lot. The existence of this contract system also has a positive value, namely by helping farmers who experience difficulties when selling their commodities and helping farmers not to experience large losses. The process of the contract system is said to violate Islamic business ethics because it clearly violates the rules by taking advantage of the difficulties experienced by them. When farmers experience difficulties, although not everyone in this contract process takes advantage of the difficulties, there are several benefits that arise from the existence of this contract system, such as helping farmers not to experience losses.